2020
DOI: 10.1111/vru.12896
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic vertebral left atrial size: A reference interval study in healthy adult dogs

Abstract: Thoracic radiography is a useful technique for the evaluation of cardiac dimensions, especially when echocardiography is not possible. The vertebral left atrial size (VLAS) has recently been proposed as a new radiographic method for quantifying left atrial dimensions in dogs. The aims of this retrospective, reference interval, observational study were to describe values for VLAS in a group of healthy adult dogs and to compare intraobserver and interobserver agreement for VLAS versus vertebral heart score (VHS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
29
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 24 publications
(38 reference statements)
10
29
3
Order By: Relevance
“…A recent study has also shown that VHS is influenced by the cardiac cycle but VLAS is not 36 . Our data suggest that in a dog with suspected cardiovascular disease, if VLAS is increased above normal (ie, >2.3 vertebrae) 19 clinicians can be reasonably confident the LA is enlarged. Conversely, if VHS is increased (using breed‐specific cutoffs or VHS >10.7 18 if mixed‐breed), there is approximately a 40% chance the LA is not enlarged (false negative).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…A recent study has also shown that VHS is influenced by the cardiac cycle but VLAS is not 36 . Our data suggest that in a dog with suspected cardiovascular disease, if VLAS is increased above normal (ie, >2.3 vertebrae) 19 clinicians can be reasonably confident the LA is enlarged. Conversely, if VHS is increased (using breed‐specific cutoffs or VHS >10.7 18 if mixed‐breed), there is approximately a 40% chance the LA is not enlarged (false negative).…”
Section: Discussionsupporting
confidence: 54%
“…If unavailable or a mixed‐breed, normal VHS was considered to be ⩽10.7 vertebrae 18 . Normal VLAS was considered to be ⩽2.3 vertebrae 19 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, most studies reporting breed-specific reference values of the VHS included a maximum of 30 cases per breed. 5,6,[10][11][12]14,26 Finally, similar to previous studies on radiographic vertebral-based measurement, 11,16,27,28 our sample population did not include dogs younger than 12 months. Based on our review of the literature, there are no large studies published that attest whether young age and skeletal immaturity can have a significant influence on vertebral-based measurement.…”
Section: Discussionmentioning
confidence: 99%